Total phenolic content and antioxidant activity of roselle (Hibiscus sabdariffa) extracts - Haron, Normah; Mat Jusoh, Hanapi; Abul@Abdul Rahman, Syuhaida (Kulliyyah of Allied Health Sciences, International Islamic University Malaysia., 2019)
Introduction: Roselle (Hibiscus sabdariffa) is widely known for its benefits and medicinal properties. The aims of this study were to determine the total phenolic content (TPC) in H. sabdariffa extract, its antioxidant activity and relationship between TPC and its antioxidant scavenging capacity. Methods: The TPC value for each extract of free, bound soluble and bound insoluble phenolic acids was determined by using Folin-Ciocalteu assay. The antioxidant scavenging capacity was evaluated by using DPPH assay. Results: The results obtained in this study showed that bound soluble phenolic acids (7.63 + 0.28 mg GAE/g DW) had the highest TPC value than the free and insoluble phenolic acid extracts (2.78 + 0.20 mg GAE/g DW and 3.61 + 0.85 mg GAE/g DW, respectively) (p<0.05). As for the IC50 values, bound soluble phenolic acid extract exhibited the greatest value(0.62%) as compared to the free and bound insoluble phenolic acid extracts (0.90% and 1.14%, respectively). A positive correlation (R2 = 0.956) between three extracts (free, soluble and insoluble phenolic acids) of TPC and antioxidant radical scavenging capacity (DPPH) was obtained. Conclusion: It can be concluded that phenolic acids in H. sabdariffa extracts have an effect to the antioxidant scavenging capacity particularly in the bound soluble form. This finding proved that H. sabdariffa extracts could be a good source of natural antioxidant for food, cosmetic and pharmaceutical industries.